Case report: Nerve fiber regeneration in children with melanocortin 4 receptor gene mutation related obesity treated with semaglutide - Gad, Hoda; Mohammed, Idris; Dauleh, Hajar; Pasha, Maheen; Al-Barazenji, Tara; Hussain, Khalid; Malik, Rayaz A. (Frontiers in Endocrinology, 2024)
Melanocortin 4 receptor (MC4R) mutations are the commonest cause of monogenic obesity through dysregulation of neuronal pathways in the hypothalamus and prefrontal cortex that regulate hunger and satiety. MC4R also regulates neuropathic pain pathways via JNK signaling after nerve injury. We show evidence of corneal small fibre degeneration in 2 siblings carrying a heterozygous missense variant c.508A>G, p.Ille170Val in the MC4R gene. Both children were treated with once weekly semaglutide for 6 months with no change in weight, and only a minor improvement in HbA1c and lipid profile. However, there was evidence of nerve regeneration with an increase in corneal nerve fiber density (CNFD) (child A (13.9%), child B (14.7%)), corneal nerve branch density (CNBD) (child A (110.2%), child B (58.7%)) and corneal nerve fiber length (CNFL) (child A (21.5%), child B (44.0%)).